Mediastinal Bronchogenic Cysts: Demonstration of Fluid-Fluid Level in Bronchoscopic US Imaging. Issue 2 (April 2017) - Han, Se Eun; Kwon, Woon Jung; Cha, Hee Jeong; Lee, Young Jik; Lee, Taehoon; Seo, Kwang Won; Jegal, Yangjin; Ahn, Jong-Joon; Ra, Seung Won
Abstract : We report the findings for 2 patients with a fluid-fluid level seen on endobronchial ultrasound (EBUS) images of bronchogenic cysts. The EBUS images demonstrated a well-circumscribed cyst with a fluid-fluid level showing an anechoic upper part and a relatively hyperechoic lower part. A fluid-fluid level on EBUS imaging of a bronchogenic cyst, which can help confirm the cystic nature of the lesion, has not been previously reported. EBUS-based confirmation of these cysts using fluid-fluid levels may help avoid unnecessary aspiration of the lesions.